Innovation ecosystems in the bioeconomy - Philp, Jim (OECD Science, Technology and Industry Policy Papers, 2019)
"Innovation ecosystems in the bioeconomy" examines the policy aspects of building the industrial and innovation ecosystems and value chains needed to make a bioeconomy viable as a sustainable means of production. While building biorefineries is more like a formulaic exercise in engineering, enabling these ecosystems and their value chains is a much more complex endeavour. Building on qualitative case studies and face-to-face interviews in eleven participating countries, the study reveals the diverse ways countries are seeking to achieve the goals set by national strategies and policies. The current report draws lessons from this diverse set of national case studies to generate both common and country-specific insights that can enable this transition from a fossil-based economy to a more sustainable one. These lessons include the need for systems-based approaches, attention to policy alignment, more focus on demand-side instruments, diversification of products, enabling medium-sized companies and harnessing converging technologies